Exploring Paradiplomacy Pathways: Local Government and Foreign Direct Investment Corporation Partnerships for Sustainable Development - Ahmad Harakan; Ahmad Taufik (Journal of Government and Politics (JGOP), 2023)
The present article delineates the collaboration between the Government of East Luwu Regency (Local Government) and PT. Vale Indonesia, Tbk, (Corporation) as a case in point of executing paradiplomacy to achieve sustainable development objectives. The findings of the qualitative research reveal that PT. Vale Indonesia, Tbk., has made a noteworthy contribution to the growth of the local economy and the development of infrastructure through its strategic partnership. Meanwhile, the government of East Luwu Regency has ensured adherence to the principles of sustainable development. The present investigation also highlights the primary obstacles encountered in the execution of paradiplomacy, such as ensuring a fair allocation of advantages and involving the community in the decision-making procedures. The present study substantiates the significance of paradiplomacy as a tactical instrument for attaining sustainable development and highlights the possibility of collaboration between subnational governments and transnational corporations in accomplishing this objective.